(untitled) (mathematica didactica, 2021)
This article describes a long-term-training (1.5 years included into regular lessons) to increase the competence of problem solving in an eighth (later ninth) grade class and the accompanying research; another class served as a control group. The conception of the training will be described in general and exemplarily illustrated by a detailed presentation of the unit about auxiliary lines. The results of the accompanying research indicate a success of the training: While the trained class showed no significant differences in regular curricular tasks, they achieved significantly better results referring to tasks requiring problem solving.